Model Analisis Rantai Nilai untuk Implementasi Inventaris Odoo Berbasis Perencanaan Sumber Daya Perusahaan (ERP) Menggunakan Metode Accelerated SAP (ASAP) - Felix Gratia Mangatur Manullang; Nadia Nada Farhani; Dewi Hajar (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
The automotive service industry faces escalating challenges in inventory management, necessitating digital transformation strategies that can overcome traditional operational limitations. This research explores the implementation of the Odoo Enterprise Resource Planning (ERP) system at Tama Jaya Motor, utilizing the Accelerated SAP methodology to address critical inventory management challenges such as inaccurate stock recording, inefficient goods movement tracking, and delayed procurement processes. However, this study identifies that the main issues in inventory management can hinder operational efficiency and business competitiveness. Here we propose a systematic approach using Porter's value chain analysis to map and optimize business functions across primary and supporting activities, focusing on integrating Sales, Inventory, Operations, Finance, and Customer Service modules. The implementation results demonstrate significant operational improvements, including increased stock recording accuracy, reduced procurement decision-making time, and improved service time efficiency. These findings contribute to the knowledge of the transformative potential of integrated information systems in automotive service businesses, offering a robust framework for digital transformation that enhances operational efficiency, reduces costs, and improves overall business competitiveness. In a broader context, this research not only addresses immediate technological needs but also provides insights into strategic digital integration, highlighting the critical role of advanced ERP systems in modern business management. Ultimately, this study presents a practical approach to navigating the complexities of technological innovation in service-oriented industries, demonstrating how systematic implementation can drive meaningful operational improvements.